Strategi Penguatan Budaya Mutu di Satuan Pendidikan: Sintesis Temuan Utama dari Literature Review 2020–2025 - Fajrin Afandi; Natasya Salsa Sabila; Nadia Khumairoh; Mu’alimin Mu’alimin (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Quality culture in educational institutions has become a strategic issue to improve learning service quality and school accountability. However, its implementation still faces challenges such as limited human resources, resistance to change, and weak sustainable quality management strategies. This study aims to answer the question: how are the implementation strategies and supporting factors in strengthening quality culture within educational institutions based on previous research findings? This study employs a Literature Review (LR) method by collecting scientific articles from Google Scholar and Publish or Perish (PoP) using the keyword “budaya mutu” (quality culture) with a publication range from 2020 to 2025. From a total of 30 identified articles, a screening and eligibility process was conducted, resulting in 5 main articles analyzed thematically. The synthesis reveals three key themes: (1) the role of leadership and Total Quality Management (TQM) in reinforcing quality culture, (2) the application of the PPEPP/MBBS cycle for sustainable educational quality, and (3) supporting factors and challenges in developing a culture of quality. In conclusion, strengthening quality culture requires effective leadership, systematic management strategies, and cross-sector collaboration; future research is encouraged to develop field-based intervention models to test the effectiveness of quality culture strategies.